Is separating obstetrics from gynaecology the way forward? A UK perspective - Marwan Habiba (Taylor & Francis Group, 2023)
A recent editorial in this Journal argued that increasing surgical complexity coupled with more limited training calls for separating obstetrics from gynaecology. The speciality suffers manpower challenges and high attrition rates. There is an apparent gulf in approach between researchers focussing on the views of UK graduates or trainees and workforce planners who address the problem through overseas recruitment. Whilst available literature provides scant, if any, indication as to how to address current challenges, it is important that advocates for women's health assess and mitigate potential drawbacks when exploring the way forward.